The drama therapy core processes: A Delphi study establishing a North American perspective. (September 2022) - Frydman, Jason S.; Cook, Angelle; Armstrong, Calli Renee; Rowe, Chyela; Kern, Chelsi
Abstract: Over the past decade, several initiatives have been launched to increase empirical research in drama therapy. In alignment with this intention, the drama therapy core processes were investigated to establish communal conceptualization and advance operationalization. A Delphi method was modified and utilized to determine makeup, verbiage, and scope of these distinct elements of practice according to North American drama therapists ( N = 30). The study was conducted over four rounds, initially inviting expert original panelists ( n = 5) to review and edit iterations of previous core processes and subsequently utilizing additional evaluators ( n = 25) to provide consensus ratings and feedback on these revisions. Among additional evaluators, inter-rater reliability met threshold criteria for each core process, advancing consensus-derived definitions. Notable changes occurred through the Delphi process, including the elimination, integration, and addition of several core processes. The finalized schematic featured a tripartite definition format for each of the following seven core processes: active witnessing, distancing, dramatic play, dramatic projection, embodiment, engagement in dramatic reality, and multidimensional relationship. This study communally and systematically conceptualizes and supports the operationalization of core process definitions. Considerations for future research directions are offered. Highlights: The drama therapy core processes are in session process variables that require systematic investigation for empirical understanding. As determined via a communal inquiry, a newly devised schematic features seven drama therapy core processes. Each core process within the schematic now has a tripartite definition structure dedicated to conceptualization, application, and operationalization. Specific indicators within each definition lend themselves to observation, promoting the possibility for measurement.